2018
DOI: 10.1080/10715762.2018.1466391
|View full text |Cite
|
Sign up to set email alerts
|

Allylpyrocatechol attenuates methotrexate-induced hepatotoxicity in a collagen-induced model of arthritis

Abstract: The cornerstone of treatment for rheumatoid arthritis is low dose methotrexate (MTX), but its use is limited by concerns regarding its potential for hepatotoxicity. Allylpyrocatechol (APC), a phytoconstituent sourced from leaves of Piper betle demonstrated antioxidant, anti-inflammatory, and antiarthritic properties. The present study aimed to evaluate the combined effect of APC and MTX on limiting progression of lipopolysaccharide accelerated collagen-induced arthritis, along with reduction of MTX-induced hep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 45 publications
2
3
0
Order By: Relevance
“…According to previous studies, MTX increases IL-6, TNF-α, and IL-1β levels. 39,47,60,61 Also, the inflammatory markers significantly reduced in the FA +MTX groups in the current study. These findings are in line with previous studies, indicating the FA potential to thwart the CCl 4 -induced release of inflammatory factors.…”
Section: Dovepresssupporting
confidence: 53%
“…According to previous studies, MTX increases IL-6, TNF-α, and IL-1β levels. 39,47,60,61 Also, the inflammatory markers significantly reduced in the FA +MTX groups in the current study. These findings are in line with previous studies, indicating the FA potential to thwart the CCl 4 -induced release of inflammatory factors.…”
Section: Dovepresssupporting
confidence: 53%
“…These results are consistent with a previous study showing that systemic exposure and mean residence time of methotrexate were increased by oral administration of glycyrrhizin and methotrexate (14). However, in that report, the dosage was 5 mg/kg methotrexate, and the route of administration was oral, assuming a low dose of methotrexate (5-25 mg/week) as in clinical use for rheumatoid arthritis (15,16). High-dose methotrexate was 8-12 g/m 2 (17)(18)(19)(20); in other words, the dose of methotrexate was 100-300 mg/kg per week in patients with osteosarcoma and 30-100 mg/kg per week in patients with lymphoma and leukemia.…”
Section: Figure 3 Plasma Concentration-time Profiles Of Alanine Aminotransferase (Alt) In Rats After Intravenous Administration Of Mtx Atsupporting
confidence: 91%
“…As a result we found that PCr extract has an anti-inflammatory activity and that MTX-induced caspase-3 and TNF-alpha increase could be prevented by treatment. One of the liver fibrosis parameters is the amount of tissue collagen present (36). It has already been proven by various researchers that MTX tends to increase the level of tissue collagen (37).…”
Section: Discussionmentioning
confidence: 99%